Condition monitoring approach for permanent magnet synchronous motor drives based on the INFORM method - Arellano-Padilla, J.; Sumner, M.; Gerada, C. (Institution of Engineering and Technology, 2016)
This paper proposes a monitoring scheme based on saliency tracking to assess the health condition of PMSM drives operating under non stationary conditions. The evaluated scheme is based on the INFORM methodology, which is associated to the accurate sensorless control of PM drives without zero speed limitation. The result is a monitoring scheme that is able to detect faults that would be very difficult to evaluate under nonstationary conditions. A relevant aspect of the proposed scheme is that it remains valid for full speed range, and can be used for standstill operation. Additionally, the approach is insensitive to the inverter nonlinearities which enhance the detection capabilities further respect to similar topologies. In this work the proposed approach is evaluated numerically and experimentally in the presence of incipient winding faults and inter-turn short circuits in a PM conventional drive. The obtained results show quick response and excellent detection capabilities not only in the detection of faults, but to determine their magnitude which is vital to avoid further degradation.